Service Quality, Customer Value, and Trust on Three-Star Hotel Loyalty in Batam: Satisfaction as Mediator - Rusmilee Rusmilee; Bambang Satriawan; Sajiyo Sajiyo (Jurnal Bisnis dan Pemasaran Digital, 2026)
Purpose: This study examines the effects of service quality, customer value, and trust on customer loyalty, with customer satisfaction as a mediating variable, among guests of three-star hotels in Batam City, Indonesia.Research Methodology: An explanatory quantitative design was employed. Data were collected through structured questionnaires from 125 guests who had stayed at a three-star hotel in Batam within the previous six months and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS. Results: Service quality (?=0.386), customer value (?=0.376), and trust (?=0.336) positively and significantly affect satisfaction. Loyalty is directly influenced by service quality (?=0.166), trust (?=0.235), and satisfaction (?=0.553), while customer value has no significant direct effect (?=0.042; p=0.484). Satisfaction mediates all three relationships, partially for service quality and trust and fully for customer value. The model explains 68.0% of satisfaction and 73.0% of loyalty variance.Conclusions: In three-star hotels, value for money does not automatically generate loyalty but must first translate into satisfaction.Limitations: The cross-sectional, self-reported, single-city, and single-tier design limits causal inference and generalizability. Contributions: The study demonstrates differentiated mechanisms underlying customer loyalty: Service quality and trust maintain direct effects, whereas customer value operates exclusively through satisfaction. These findings refine relationship-marketing and expectancy-disconfirmation perspectives and support mechanism-specific retention strategies in midscale hospitality.